Collective Memory in Ukraine as a Factor in Identity Formation in the Context of Postmodernity - Vitov, Andrii; Tymofieieva, Halyna (Skhid : analitychno-informat͡s︡iĭnyĭ z͡h︡urnal, 2025)
This article explores the problem of collective memory as a foundation for the construction of Ukrainian collective identity. The authors argue that identity formation in the postmodern era is characterized by personalization, flexibility, and the ambivalent influence of globalization. The study demonstrates that Ukrainian collective memory represents a polyphony of interpretations rather than a homogeneous reflection of the past. Its competitive and composite nature is conceptualized not as a weakness, but as a source of pluralism, adaptability, and potential for critical re-evaluation. Accordingly, memory politics in Ukraine is presented as an active process of shaping a desired society. The article emphasizes that in the context of postmodernity and the Russian-Ukrainian war, collective identity in Ukraine is transforming into a dynamic, flexible, and personalized project. This process strongly correlates with Michel Foucault’s concepts of the "technologies of the self," which in the Ukrainian context evolve into ethical, cultural, and historical practices, shaping collective identity as a reflexive and open construction. Through war, memory, and solidarity, Ukrainian society not only defends its statehood but also creates a new moral and symbolic reality, where the personal and national, ethical and aesthetic, private and political are inextricably intertwined. The construction of a distinct national narrative and Ukraine’s postcolonial awakening are shown to be accompanied by the formation of unique historical conceptions, the affirmation of the Ukrainian language, the emphasis on European values, and the deconstruction of shared Russian-Ukrainian myths.